DIVERSITY OF SMALL NON-VOLANT MAMMALS IN THE CENTER FOR ECOLOGICAL DEVELOPMENT AND RECREATION (CEDAR), BUKIDNON, PHILIPPINES - Jasmin Rizalda; Dave Buenavista (SEAMEO BIOTROP, 2026)
ARTICLE HIGLIGHTS- Six murid rodent species, including one endemic and five non-native species, were recorded in CEDAR, Bukidnon.- Semi-natural habitats were dominated by endemic (Rattus cf. everetti), while human-modified habitats were dominated by non-native rodents.- Human-modified habitats had higher rodent diversity than semi-natural habitats.- Rattus tanezumi and Rattus cf. exulans adapted to both habitat types.- Semi-natural habitats are vital for conserving native rodent diversity.ABSTRACTThis study assessed the diversity and species composition of murid rodents in two habitat types: semi-natural and human-modified within the Center for Ecological Development and Recreation (CEDAR) in Impasug-ong, Bukidnon, Philippines. A total of 640 trap nights were conducted using live traps across both habitats, yielding six (6) rodent species: one (1) native (Rattus cf everetti) and five non-native species (Rattus cf exulans, Rattus cf norvegicus, Rattus tanezumi, Mus musculus, and an unidentermined Rattus species). Station 1 (semi-natural habitat) was dominated by the native species, while Station 2 (human-modified habitat) was dominated by non-native species. Diversity analysis using the Shannon-Wiener Index showed higher diversity in the human-modified habitat (H’ = 1.280) compared to the semi-natural habitat (H’ = 1.004), supporting the hypothesis that habitat modification influences rodent diversity. The exclusive presence of R. cf. everetti in the semi-natural habitat emphasizes the sensitivity of native species to disturbance while R. tanezumi and R. cf. exulans were found in both habitats, indicating their adaptability to varied environments. These findings support the hypothesis that habitat modification influences rodent diversity and human-modified habitat are more species rich dominated by non-native species. The study highlights the importance of conserving semi-natural habitats and highlights the utility of rodents as bioindicators for assessing ecological integrity in forest habitats. The study recommends broader mammalian surveys, wildlife monitoring, and the regulation of wildlife reintroduction in CEDAR.